ANALISIS MODEL PENGEMBANGAN KURIKULUM SISTEM FULL DAY SCHOOL DI SMP NEGERI SE-KECAMATAN LIMBOTO KABUPATEN GORONTALO - Imam Mashudi; Sudarsono (LP2M Universitas Bina Mandiri Gorontalo, 2018)
This research aims to know the Curriculum Development Model of Full Day School System in State Junior High School All of Limboto Sub-districts, Gorontalo District, and to know the supporting and inhibiting factors of Curriculum Development of Full Day School System in State Junior High School All of Limboto Sub-districts, Gorontalo District. This research uses a qualitative approach which will be implemented in State Junior High School All of Limboto Sub-districts, Gorontalo District. Data collection techniques used are observation technique, interviews and documentation, with the data analysis technique used is an interactive model analysis. This research produces several points, namely: (1) Curriculum of Full Day School System implemented in the form of literacy activities which starts before teaching and learning activities and after teaching and learning activities (KBM) are scheduled with extracurricular activities, namely scouts, arts and sports according to what students are interested in. (2) supporting factors this Full Day School System more to put forward a few points namely can shape the students' character, Extracurricular activities are more effective, can help students doing homework rather than to playing outside, and can help students more discipline. Whereas, for the inhibiting factor of this system is sports and art facilities incomplete and literature books are still lacking